The new Indo-Pacific order: relations between China, India, and the United States the 21st century - Luo, Yanchao (Вестник Томского государственного университета. История)
The article discusses the concept of the Indo-Pacific region, the reaction of world leaders to it, the geopolitical interests of these countries in the Indian Ocean, the goals of their policies, the specifics of the strategy for their achieve-ment and interaction. These issues are explored through comparative, comparative-historical and systemic analysis, as well as a geopolitical approach to the study of global problems. Various forms of cooperation are being formed in the re-gion, which have either a pronounced anti-Chinese or forced pro-Chinese character, which leads to an increase in tension between the countries.